Numerical investigation of infrared imaging of multi-UAV formation under cloud and rain weather conditions - Gao, Wenqiang; Zhang, Teng; Tang, Enling; Zhang, Pengjun; Niu, Qinglin (Frontiers in Physics, 2025)
Infrared imaging is essential for detecting multiple unmanned aerial vehicle (UAV) targets detection to capture flight altitude and behavior. This study focused on a typical stealth UAV formation with a flying-wing configuration. Considering the attenuation effects of clouds and rain on the infrared spectrum, a ground-based infrared imaging algorithm was developed. Infrared radiation imaging was conducted using the apparent ray tracing method and mesh clipping technology. The infrared radiation intensity distribution of the UAV formation target within the 8.0–12.0 μm band was calculated, and infrared thermal images incorporating the occlusion effect were obtained. The results showed that the radiance of the multi-UAV formation was approximately 8.0 × 10−5 W/Sr, which was 103–104 orders of magnitude lower than that under standard atmospheric conditions under cloudy weather conditions. The infrared radiance was approximately 1.7 × 10−5 W/Sr, which was 104–105 lower than that under standard atmospheric conditions under rainy weather conditions.